2019
DOI: 10.1021/acs.jpcc.9b06664
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Molecular Switching via Chemical Functionality: Ethyl vs Methoxy Rotors

Abstract: Surface-bound molecular rotors provide a useful way to study the structure and dynamics of molecular motion at the single-molecule level. However, when most molecules adsorb on a metal surface, their interaction with the metal changes their properties dramatically, making a priori design impossible. We report a case in which gas-phase predictions of the stable orientations of a class of molecular rotors hold true when they are attached to a surface. This transferability is achieved by mounting the molecular ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Rotor molecules deposited on surfaces may be investigated at a submolecular scale using scanning tunneling microscopy (STM). , The compounds thus studied fall into two classes. Either molecular adsorbates serve as a rotor and the substrate is used as a stator or the stator and the rotor are subunits of the same molecule. Besides rotors there are also rotary switches that alternate between two rotation angles and consequently do not enable studies on the directionality of the motion, which is essential for using a rotor in a motor. , …”
mentioning
confidence: 99%
“…Rotor molecules deposited on surfaces may be investigated at a submolecular scale using scanning tunneling microscopy (STM). , The compounds thus studied fall into two classes. Either molecular adsorbates serve as a rotor and the substrate is used as a stator or the stator and the rotor are subunits of the same molecule. Besides rotors there are also rotary switches that alternate between two rotation angles and consequently do not enable studies on the directionality of the motion, which is essential for using a rotor in a motor. , …”
mentioning
confidence: 99%
“…Our DFT calculations confirmed that the −CH 2 CH 3 /–CH 2 CF 3 tails of intermediates and products 1, 2, and 3 are most stable when oriented perpendicular to the phenyl ring, while the methoxy tail of I 4 and P 4 are most stable when in plane with the phenyl ring (Figure S1). In Figure A, the I 1 species has relatively small charges and, based on the orientation of the organometallic intermediates, there does not seem to be a significant relationship between any local dipoles and its packing structure. However, in Figure B, the orientation of the I 2 organometallic intermediates appears to suggest a relationship as the highly electronegative fluorine groups, which are aligned with the hydrogens on the phenyl rings of adjacent intermediates.…”
Section: Results and Discussionmentioning
confidence: 98%
“…Through the use of surface techniques, such as scanning tunneling electron microscopy (STM), the formation and surface diffusion of Ullmann coupling intermediates have been studied by tracking the reaction from the starting aryl reagents, through the intermediates and to the final biaryl products, and this mechanism is summarized schematically in Figure . On a Cu(111) surface, Ullmann coupling intermediates do spontaneously self-assemble into 2D crystals and these assemblies have demonstrated interesting properties ranging from a diversity of domain types to molecular-scale machines. Due to current limitations in 2D crystal engineering, it is not yet possible to a priori predict the relationships between the molecular structure of the aryl halide precursor and the crystal packing of the intermediate and final biaryl product; oftentimes, slight changes in the starting reagent result in a huge impact on the packing structures of the intermediate and product. One of the key features of the Ullmann coupling reaction on a copper surface is that, in the intermediate stage, the aryls to be coupled are bonded to a copper atom that is removed from the surface (Figure , middle panel). ,,, Compared to the biaryl product, the intermediates are slightly larger and pack quite differently as this manuscript will show.…”
Section: Introductionmentioning
confidence: 99%
“…Figure A–C shows representative images in frequency shift, AFM tip tunneling current, and STM modes of the 2D arrays, respectively. We have previously studied the structures of these 2D molecular rotor arrays. Briefly, when 4-bromo-1-ethyl-2-fluorobenzene is deposited on a Cu(111) surface and annealed to 260 K, the C–Br bond is broken, and organometallic intermediates of the Ullmann coupling reaction form on the surface, as shown in Figure E. These organometallic intermediates spontaneously self-assemble into a variety of 2D crystal structures on the Cu(111) surface.…”
Section: Resultsmentioning
confidence: 99%